Communication in fragile X syndrome: Patterns and implications for assessment and intervention - Hoffmann, Anne (Frontiers in Psychology, 2022)
Fragile X syndrome (FXS) is the most common cause of inherited intellectual disability and is associated with a high rate of autism diagnosis. Language delays have been noted in the areas of overall communication and the specific areas of receptive, expressive, and pragmatic language, as well as in development of speech sounds and literacy. It has been widely noted that those individuals with a diagnosis of both FXS and autism tend to have more significant intellectual disability and language disorder. In this study, the research exploring the FXS language phenotype is presented, and the roles of cognition, autistic symptomatology, and gender are highlighted as possible. Implications for assessment and intervention approaches based on the strengths and weaknesses of the FXS language phenotype are provided.